Vidas/narrativas em trânsito: movimentos migratórios nas literaturas contemporâneas de língua portuguesa - Leite, Ana Mafalda; Pinheiro, Vanessa Riambau; Kralik Angelini, Paulo Ricardo (Letrônica, 2018)
—